An Analysis of the Interrelationship among Crime, Misery Index and Institutional Quality: A Case Study of Pakistan - Sanam Munir; Nabila Asghar; Hafeez ur Rehman (Journal of Political Studies, 2017)
The study investigates the impact of misery, institutional quality, human capital, population density and GDP per capita on crime in Pakistan over the period 1984 to 2015. The misery index is constructed and Johansen and Juselious test of co-integration is employed to check long run relationship among variables. VECM is used to explore short run and long run dynamics and Toda Yamamoto causality test for causal relationship. Results confirm significant long run relationship among crime and its determinants in Pakistan. Two channels of bidirectional causality are found active with human capital from GDP per capita and governance. Unidirectional causality runs from crime to misery and from misery to institutional quality .The study concludes that misery and poor quality of institutions have been contributing to higher crimes statistics in Pakistan for last three decades. Therefore, government should take steps to reduce misery and to improve institutional quality to mitigate criminal activities in Pakistan.